2017
DOI: 10.1371/journal.pone.0177098
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of microRNAs during early spermatogenesis in chicken

Abstract: Spermatogenesis is a complex process that involves many elements. However, until now, little is known at the molecular level about spermatogenesis in poultry. Here we investigated microRNAs and their target genes that may be involved in germ cell development and spermatogonial in chicken. We used next-generation sequencing to analyze miRNA expression profiles in three types of germline cells: primordial germ cells (PGCs), spermatogonial stem cells (SSCs), and spermatogonia (Sp) during early stage of spermatoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Previous studies have established functions for specific microRNAs in regulating reproduction [ 23 ]. However, only a few microRNAs and target genes involved in the development and reproduction of testis have been identified in mammals [ 23 , 24 , 25 ]. Recently, it has been reported that a total of 61 DERs and 80 DEGs have been identified between cattleyak (cattle ♂ and yak ♀ ) and yak testes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established functions for specific microRNAs in regulating reproduction [ 23 ]. However, only a few microRNAs and target genes involved in the development and reproduction of testis have been identified in mammals [ 23 , 24 , 25 ]. Recently, it has been reported that a total of 61 DERs and 80 DEGs have been identified between cattleyak (cattle ♂ and yak ♀ ) and yak testes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…musculus ) [ 29 ] and chicken ( G . gallus ) [ 30 ][ 31 ]. The role of miR-202 in gonads is not yet understood and most of what is known relies on expression data and some functional studies.…”
Section: Introductionmentioning
confidence: 99%
“…a, b: significant difference among the three species (p < .05) during early stages of spermatogenesis (Buchold et al, 2010), and piRNAs are more abundant in sperm and spermatids (Schubert, 2016). Compared to the well-illustrated mechanisms of spermatogonium development in human (Neto, Bach, Najari, Li, & Goldstein, 2016), poultry (Xu et al, 2017), rodents (Ikami et al, 2015) and some ruminants (Luo, 2014), few contributing factors have been determined to be involved in the sterility of dzo. Thus, we aimed to identify expression profiles of small RNAs in testis of cattle, yak and dzo to determine whether miRNAs and piRNAs differentially expression can be mapped to specific regulation role in development and spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%